The Myth of Originality - (:unkn) unknown (My University, 2007)
The concept of originality has always been a sensitive one in architectural design. Architects are hired for ideas and services provided to clients via architectural drawings and are the foundation of professional viability. Has the 1990 enactment of The Architectural Works Copyright Protection Act improved the overall lot of architects with regard to protection of their ideas and, by extension, their livelihood? Or, have the implications of the Act provided as many problems for architects as relief?